Mental disorders and cognitive impairment in ageing offenders. Issue 6 (1st November 2016) - Combalbert, Nicolas; Pennequin, Valérie; Ferrand, Claude; Vandevyvère, Rémy; Armand, Marine; Geffray, Brigitte
Abstract: The aim of our study was to identify psychiatric and cognitive disorders among older prison inmates and to investigate whether there is an association between mental disorders and cognitive impairment. 138 men aged 50 and over were recruited in seven French prisons (Group 1) and 138 men aged 50 and over were recruited from the general public (Group 2). Participants were assessed using the Mini International Neuropsychiatric Interview, the Mini Mental State Examination, and the Frontal Assessment Battery. The results reveal very significant differences in the incidence of mental disorders and in cognitive performance between the two groups. However, there does not appear to be a significant link between mental disorders and cognitive performance. We discuss the risk factors for mental disorders and cognitive impairment. We raise particularly the issue of depression, which is the most common pathology in this population and which is generally associated with the risk of suicide.